DAMPAK HARGA LOGISTIK YANG TINGGI BAGI KOMODITI BERAS - Nurakhdan, Radithya; Dwihanggara, Maynard Dias; Pratama, Iqbal Ardyas; Wikansari, Rinandita (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This research focuses on evaluating the impact of high logistics costs on rice trade in Indonesia in the context of rapid industrial development and the digital era 4.0. Rice price data from various countries is processed to examine its relationship with logistics costs. The main findings confirm that high logistics costs in Indonesia hinder the rice export-import process, especially at the procurement stage. Factors such as transportation costs, storage and logistics administration play a role in changing the dynamics of rice trade. Comparison of shipping costs between countries shows the difficulties faced by the Indonesian logistics industry, with the proportion of logistics costs to GDP still high when compared to neighboring countries. Lack of logistics infrastructure, a deficit of skilled human resources, and an inefficient distribution system are also the main triggers for high logistics costs in Indonesia. Therefore, concrete steps from the government are urgently needed to improve infrastructure and logistics systems, in order to reduce high logistics costs so that trade and rice price stability are guaranteed in Indonesia.